Analysis of Reading Difficulties in Indonesian Language Learning Among Year 3 Pupils at SDN Saruni 4 - Suhani; Ajeng Muliasari; Omah Mukarromah; Yeni Sulaeman (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
The present study discusses the reading fluency difficulties of second-grade students at SDN Saruni 4 and identifies the factors underlying their reading ability. This study uses a qualitative descriptive approach. Data were collected through interviews with second-grade Indonesian language teachers and documentation of student learning outcomes. The results reveal that most students had achieved reading fluency but still experienced difficulties in pronunciation, intonation, and reading comprehension. Factors that influence reading fluency include internal factors, such as students' psychological conditions and motivation to learn, and external factors, such as parental support, family environment, and teachers' instructional methods. Efforts by teachers to overcome these problems include establishing reading literacy activities as a habit before learning begins, providing continuous motivation and support, and implementing varied, effective learning methods and strategies to improve students' reading abilities.